Investigating the impact of type I-E CRISPR-Cas systems and acrEI10 on multidrug-resistance in clinical isolates of Klebsiella pneumoniae - Maryam Siroosi; Fatemeh Ghasemi; Fereshteh Jabalameli; Mohammad Emaneini; Mohammadreza Salehi; Reza Beigverdi; Mohammad Ali Amoozegar (PLoS ONE, 2025)
Klebsiella pneumoniae is a pathogen related to nosocomial infections with a high rate of antibiotic resistance. The aim of this study was to understand the impact of the presence of CRISPR-Cas systems and an anti-CRISPR gene on multidrug-resistance in K. pneumoniae isolates. The study analyzed 100 clinical K. pneumoniae isolates obtained from a hospital setting. The investigation involved determining antibiotic resistance profiles, including ESBL production, identifying specific carbapenemase and aminoglycoside resistance genes, detecting the presence of CRISPR-Cas systems, identifying the anti-CRISPR gene acrEI10 , and sequencing CRISPR arrays. Correlation analysis between resistance genes and CRISPR-Cas systems was also performed. All isolates in this study were determined to be multidrug-resistant (MDR), with resistance rates exceeding 70% for the majority of antibiotics tested. The most prevalent carbapenemase genes were bla OXA-48 and bla NDM , while aminoglycoside resistance was primarily mediated by aac( 6 ´)-Ia and ant(2")-Ia . Only 7% of the isolates harbored CRISPR-Cas systems and the gene acrEI10 , which encodes an anti-CRISPR protein, was detected in one of the CRISPR-Cas positive isolates. Sequencing of the CRISPR array from this isolate showed similarities between the spacers and sequences found in plasmids and K. pneumoniae chromosome. No strong correlation was identified between the antibiotic resistance genes and CRISPR-Cas systems. Findings from this study suggest a complex interplay between these factors in MDR isolates of K. pneumoniae and show that further investigations are needed to have a better understanding of the mechanisms related to the coexistence of these elements and their impact on dissemination of antibiotic resistance genes.